SCHOOL LEADERSHIP, PERSONALITY, DAN MOTIVASI, TERHADAP PROFESIONALISME GURU SEKOLAH DASAR - Nurhayati, Nurhayati (Pascasarjna Universitas Negeri Jakarta, 2016)
Abstract : The study aims to determine the impact of school leadership, personality, and motivation in the professionalism of teachers of State Primary School. Data analysis technique used is path analysis. Data population was selected by random sampling, from 10 groups selected one group, about 82 teachers. Data was obtained by questionnaire which has been tested. In conclusion, professionalism of teacher in state primary schools, has a variety of characteristics, professionalism of teachers influenced either by several variables, including the school leadership, personality, and motivation. The implication is that the professionalism of teachers will increase if there is, good school leadership, good personality of a teacher, and high teacher motivation.Keyword : school leadership, personality, motivasionAbstrak : Penelitian bertujuan untuk mengetahui pengaruh school leadershif, personality, dan motivasi terhadap profesionalisme guru Sekolah Dasar. Teknik analisis data yang digunakan adalah analisis jalur. Populasi data dipilih secara Random Sampling, dari 10 gugus terpilih satu gugus, sebanyak 82 guru. Data diperoleh dengan angket yang telah diuji coba. Kesimpulannya, profesionalisme guru Sekolah Dasar, memiliki keragaman karakteristik, profesionalisme guru dipengaruhi oleh beberapa variabel, diantaranya, school leadership, kepribadian personality, dan motivasi. Implikasinya bahwa profesionalisme guru akan semakin meningkat apabila terdapat school leadership yang baik, personality guru yang baik, dan motivasi guru yang tinggi.Kata kunci : profesionalisme guru, school leadership, personality, motivasi